Multiple cytochrome P450 genes: conferring high levels of permethrin resistance in mosquitoes, Culex quinquefasciatus - Yang, Ting (Sci Rep, 2021)
Insecticides, especially pyrethroids, are the most important in the insect pest control and preventing insect vector-borne human diseases. However, insect pests, including mosquitoes, have developed resistance in the insecticides that used against them. Cytochrome P450s are associated with insecticide resistance through overexpression and detoxification mechanisms in insect species. In this study, we utilized a powerful tool, the RNAi technique, to determine the roles of key P450 genes overexpressed in permethrin resistant mosquitoes that confer insecticide resistance to unravel the molecular basis of resistance mechanisms in the mosquito Culex quinquefasciatus. The results showed that knockdown of 8 key P450 genes using RNAi techniques significantly decreased resistance to permethrin in resistant mosquitoes. In silico modeling and docking analysis further revealed the potential metabolic function of overexpressed P450 genes in the development of insecticide resistance in mosquitoes. These findings not only highlighted the functional importance of these P450 genes in insecticide resistance, but also revealed that overexpression of multiple P450 genes was responsible for the high levels of insecticide resistance in a mosquito population of Culex quinquefasciatus.